Przemiany w produkcji i handlu miodem w Polsce - Madras-Majewska, Beata; Majewski, Janusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2002)
The article treats about the bee keeping which is very impo1iant element of agriculture. Bee pollination of plants is the evidence of significant role the bees play in the environment. Bee colonies produce honey, propolis, bee wax and bee bred. In Poland, the bee keeping's situation has worsened since the middle of the eighties. The number of apiaries has decreased fourfold and the pace of growth in the number of bee's trunks has been three times slower in the end of the nineties. Furthermore, honey production fell from 14.1 thousand tons in 1991 to about 9 thousand tons in 2000. Poland's share in world production of honey reached only 0,8 per cent in 1998.